Aprendizaje servicio: una metodología para aprender y desarrollar la responsabilidad social en estudiantes de pedagogía de la Universidad Arturo Prat, Iquique, Chile (Contextos: Estudios de Humanidades y Ciencias Sociales, 2017)
The following article aims at analyzing the advantages and benefits Service learning may bring to the students of the teacher-training program at Universidad Arturo Prat, in Iquique, Chile. It is a way to approach in-service practice to future teachers and to contribute signifi- cantly to their integral training period collecting as models successful experiences of other institutions such as Universidad de Chile and Pontificia Universidad Católica de Chile since 2004.